2013
DOI: 10.1051/limn/2013045
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient silica sink in monomictic Lake Biwa in Japan

Abstract: -In order to clarify the mechanisms underlying high efficiency of the silica sink in monomictic Lake Biwa in Japan, vertical flux of biogenic silica (BSi) was measured using sediment traps over a period of 15 months. The sediment traps were deployed at depths of 30 and 70 m. On a global scale, BSi fluxes in Lake Biwa were very high, ranging from 20 to 1087 mg Si.m In the winter period, when nutrients are supplied from the hypolimnion to the epilimnion, the distribution of photosynthetically active diatoms was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…SiO 2 loading from the South ranged from 2,500 to 8,000 tons yr -1 . The estimation for the SiO 2 sink represented by Goto et al (2013) showed that 20,000 ton SiO 2 yr -1 was retained in Lake Biwa, which accounts for 80% of the annual inflow. Figure 5b shows the estimated seasonal change in nutrient loading from rivers and groundwater.…”
Section: Resultsmentioning
confidence: 99%
“…SiO 2 loading from the South ranged from 2,500 to 8,000 tons yr -1 . The estimation for the SiO 2 sink represented by Goto et al (2013) showed that 20,000 ton SiO 2 yr -1 was retained in Lake Biwa, which accounts for 80% of the annual inflow. Figure 5b shows the estimated seasonal change in nutrient loading from rivers and groundwater.…”
Section: Resultsmentioning
confidence: 99%